Formulasi dan Evaluasi Sediaan Masker Gel Peel-Off Ekstrak Etanol Daun Jambu Bol (Syzygium malaccence (L.) Merr. & Perry) untuk Perawatan Kulit Wajah - Sri Hainil; Sri Budiasih; Habibie Deswilyaz Ghiffari; Senny Mey Pratiwi; Desy Maniarti Gusmali (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The guava plant, also known as Syzygium malaccense (L.) Merr. & Perry, is a member of the Myrtaceae family and is rich in antioxidants. The therapeutic properties of this plant have been known for centuries. When compared to other sections of the guava plant, the leaves have the largest concentration of flavonoids. The purpose of this research is to develop and assess the physical characteristics of five different formulations of a peel-off gel mask containing guava leaf extract (Syzygium malaccense (L.)) at concentrations of 0% (F0), 2% (F1), 4% (F2), 8% (F3), and 12% (F5). The recipe was found to be consistent in appearance, smell, and taste throughout the organoleptic testing. The results of tests on pH, spreadability, and viscosity were statistically different (p0.05). Results from 4°C viscosity tests showed a range of 3933-7167 Cps. pH values ranged from 5.08 to 6.48 and spreadability from 5.23 to 6.50 cm when tested at 4, 25, and 40 degrees Celsius, respectively. The drying time test at 25°C and 40°C revealed no significant variations (p>0.05), and the viscosity test yielded values between 4100 and 4933 Cps at both temperatures. Ten test subjects were not irritated by any of the tested formulations. Finally, F4 (0.8%) showed the finest physical quality when incorporated into a guava leaf extract peel-off gel mask.